2021
DOI: 10.21203/rs.3.rs-354711/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ascorbic Acid as an Adjunctive Therapy in Critically Ill Patients with COVID-19: A Multicenter Propensity Score Matched Study

Abstract: Background: Ascorbic acid represents an appealing option for clinicians to utilize in the context of a global health pandemic of COVID-19 patients due to its proposed clinical efficacy, relative safety, and low cost.Objectives:The aim of this study was to evaluate the efficacy and safety of using ascorbic acid in supplemental dose as adjunctive therapy in critically ill patients with COVID-19. Methods: This was a multi-center, non-interventional, retrospective cohort study. All critically ill adult patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…(38) Most trials evaluated the role of oral ascorbic acid in critically ill patients failed to show improved outcomes due to limited absorption, gut ischemia, impaired intestinal flora, and different distribution. (39) Animal models showed that the lungs are very susceptible to ascorbic acid deficiency. (40) Also, early reports showed that administration of ascorbic acid was associated with increased alveolar fluid clearance and decreased epithelial permeability.…”
Section: Discussionmentioning
confidence: 99%
“…(38) Most trials evaluated the role of oral ascorbic acid in critically ill patients failed to show improved outcomes due to limited absorption, gut ischemia, impaired intestinal flora, and different distribution. (39) Animal models showed that the lungs are very susceptible to ascorbic acid deficiency. (40) Also, early reports showed that administration of ascorbic acid was associated with increased alveolar fluid clearance and decreased epithelial permeability.…”
Section: Discussionmentioning
confidence: 99%